Artificial Intelligence and Natural Language 11th Conference, AINL 2022, Saint Petersburg, Russia, April 14-15, 2022, Revised Selected Papers - Malykh, Valentin; Filchenkov, Andrey (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 11th Conference on Artificial Intelligence and Natural Language, AINL 2022, held in St. Petersburg, Russia, in April 2022. The 8 revised full papers and 1 short paper were carefully reviewed and selected from 20 submissions. The volume presents recent research in areas of of text mining, speech technologies, dialogue systems, information retrieval, machine learning, articial intelligence, and robotics. .
Inferring image background from text description -- Topical Extractive Summarization -- The Semantic Shifts of the Topical Structure in the Corpus of Lentach News Posts -- Development of folklore motif classifie using limited data -- Morphological and Emotional Features of the Speech in Children with Typical Development, Autism Spectrum Disorders and Down Syndrome -- WikiMulti: a Corpus for Cross-Lingual Summarization -- Rethinking Crowd Sourcing for Semantic Similarity -- Interplay of Visual and Acoustic Cues of Irony Perception: a Case Study of Actor's Speech -- Findings of Biomedical Russian to English Machine Translation Competition -- Translation of medical texts with ensembling and knowledge distillation.
Keywords: Artificial intelligence; Computer science; Database management; Education-Data processing; Artificial Intelligence; Theory of Computation; Database Management; Computers and Education